Alienopteris livingstonensis gen. et sp. nov., enigmatic petrified tree fern stem (Cyatheales) from the Aptian Cerro Negro Formation, Antarctica - Vera, Ezequiel Ignacio (2009)
A new genus and species of Mesozoic fern, Alienopteris livingstonensis gen. et sp. nov., is defined, based on permineralized stems recovered from the Aptian Cerro Negro Formation (Antarctica). This new taxon is characterized by the presence of Y-shaped meristeles in the stem, surrounding an heterogeneous pith, and the presence of complex petiole bases, consisting in abaxial and adaxial archs, similar to the ones present in the Cyatheaceae s.l.. Since no living nor fossil filicalean fern possesses such mixture of features, and taking into account that no leaves and reproductive structures were found, phylogenetic relationships are not clear. Two independent cladistic analysis show clear placement of Alienopteris livingstonensis among the ‘‘core tree ferns.’’